2020
DOI: 10.1186/s12866-020-01878-5
|View full text |Cite|
|
Sign up to set email alerts
|

Novel multiplex real-time PCR assays reveal a high prevalence of diarrhoeagenic Escherichia coli pathotypes in healthy and diarrhoeal children in the south of Vietnam

Abstract: Background: Diarrhoeagenic Escherichia coli (DEC) infections are common in children in low-middle income countries (LMICs). However, detecting the various DEC pathotypes is complex as they cannot be differentiated by classical microbiology. We developed four multiplex real-time PCR assays were to detect virulence markers of six DEC pathotypes; specificity was tested using DEC controls and other enteric pathogens. PCR amplicons from the six E. coli pathotypes were purified and amplified to be used to optimize P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…In addition, a swab will be collected from a child without symptoms residing in a control house. The swabs will be transported in an appropriate transport medium at ambient temperature to the study hub in Mtwara town where the specimens will be stored at − 20 °C until final processing using multiplex PCR [ 22 ]. An air sampler will be used to collect standardized air samples to detect pathogens in air samples [ 23 ].…”
Section: Methods and Study Designmentioning
confidence: 99%
“…In addition, a swab will be collected from a child without symptoms residing in a control house. The swabs will be transported in an appropriate transport medium at ambient temperature to the study hub in Mtwara town where the specimens will be stored at − 20 °C until final processing using multiplex PCR [ 22 ]. An air sampler will be used to collect standardized air samples to detect pathogens in air samples [ 23 ].…”
Section: Methods and Study Designmentioning
confidence: 99%
“…In our study, we used 16S rRNA gene sequencing to examine changes in the gut microbiome following 12 weeks of daily supplementation of either ferrous sulfate or ferrous bisglycinate in non-pregnant Cambodian women of reproductive age (WRA). We then used real-time PCR (qPCR) to assess the presence and abundance of bfpA and eae , virulence genes from enteropathogenic E. coli (EPEC), a common culprit of diarrheal disease worldwide ( 17 19 ). Due to the differences in bioavailability among the 2 iron interventions, we hypothesized that the women who received ferrous sulfate would have an increased relative abundance of pathogenic bacteria compared to those who received ferrous bisglycinate.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of DEC in Vietnamese children have been conducted so far [6][7][8]. Nguyen et al [6] reported that one or more marker genes of DEC were detected in 22.5% of fecal samples (132/587) collected from young children with diarrhea from 2001 to 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Hien et al [7] isolated DEC strains from 25.7% (64/249) of stool samples of diarrhea patients who were less than five years of age from 2001 to 2002 and classified them into pathotypes. Recently, Duong et al [8] developed new multiplex real-time polymerase chain reactions (PCRs), which revealed that 34.7% and 41.2% of stool samples from children with and without diarrhea from 2014 to 2016, respectively, were positive for the DEC pathotypes. Thus, Vietnamese children are widely contaminated with various DEC strains possibly associated with diarrhea.…”
Section: Introductionmentioning
confidence: 99%